2021
DOI: 10.1111/dth.14717
|View full text |Cite
|
Sign up to set email alerts
|

COVID ‐19 from the perspective of dentists: A case report and brief review of more than 170 cases

Abstract: A novel coronavirus which has appeared from China, has been circulating hastily around the world. We summarized the publications including oral manifestation of coronavirus disease 2019 (COVID‐19) cases based on PubMed and Google Scholar data bases, and also present a case that highlights oral lesions 2 days prior to the first COVID‐19 general symptoms. Two authors independently reviewed the papers, 17 studies of more than 170 confirmed cases between ages of 9 and 90 were included. The most common oral manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 24 publications
(75 reference statements)
1
43
0
5
Order By: Relevance
“…Another group of oral lesions seen in patients with COVID-19, but not directly related to the pathologic processes of SARS-CoV-2 infection, are opportunistic co-infections that involve the oral cavity. Oral co-infections reported thus far in patients with COVID-19 include candidiasis and Herpes simplex infections (31)(32)(33)(34)(35)(36)(37)(38)(39). As in many other debilitating diseases, the occurrence of such opportunistic co-infections is to be expected in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of oral lesions seen in patients with COVID-19, but not directly related to the pathologic processes of SARS-CoV-2 infection, are opportunistic co-infections that involve the oral cavity. Oral co-infections reported thus far in patients with COVID-19 include candidiasis and Herpes simplex infections (31)(32)(33)(34)(35)(36)(37)(38)(39). As in many other debilitating diseases, the occurrence of such opportunistic co-infections is to be expected in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were classified according to their presumed etiologies into three main categories and eight etiologic groups. In the category of oral manifestations with probable causes other than SARS-CoV-2 infection, iatrogenic lesions (lesions from intubation and other invasive procedures) (28,29), drug reactions (30), and opportunistic co-infections with Candida albicans (31)(32)(33)(34) or Herpes simplex (35)(36)(37)(38)(39) were included. The second category comprised multiorgan syndromes with variable oral manifestation.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In the present report, a large ulcer was also found on Cat-1's tongue base at the time of presentation, which may have contributed to inappetence. Various oral manifestations of COVID-19 have been reported in human patients, including dry mouth, gustatory impairment, gingivitis, sialadenitis, vesicular and ulcerative mucosal lesions predominantly located on dorsal surface of the tongue (as in our case), hard palate, and labial mucosa (45)(46)(47). The exact pathogenesis of such oral signs remains uncertain, probably involving several mechanisms, such as deterioration of the general health status, hypersensitivity of drugs used for COVID-19 treatment, stress, immunosuppression, vasculitis, and hyper-inflammatory response secondary to SARS CoV-2 infection as predisposing factors (45)(46)(47).…”
Section: Discussionmentioning
confidence: 54%
“… 4 Several reports have shown that HSV infections manifesting as oral lesions may be associated with COVID-19, although the precise manner of HSV involvement is unknown. 5 In our case, it was obvious that the herpetic glossitis developed as a result of immunosuppression due to prolonged steroid therapy, whereas judging from its clinical course and timing of onset, COVID-19 was unlikely to have contributed directly to the oral symptoms.…”
Section: Descriptionmentioning
confidence: 64%